Stressful Conditions Give Rise to a Novel and Cryptic Filamentous Form of Caulerpa cylindracea - Santamaría, Jorge; Golo, Raül; Cebrian, Emma; García, María; Vergés, Alba (Frontiers in Marine Science, 2021)
Morphological plasticity can enable algae to adapt to environmental change and increase their invasibility when introduced into new habitats. Nevertheless, there is still a lack of knowledge on how such plasticity can affect the invasion process of an invasive species. In this context, the high plasticity in the genus Caulerpa is well documented. However, after an extremely hot summer, a previously unreported filamentous morphology of Caulerpa cylindracea was detected; indeed, this morphology could only be confirmed taxonomically after in-depth morphological characterization and molecular analysis with the genetic marker tufA. We describe an ex situ culture experiment which showed that stressful conditions, such as high temperatures, can trigger this morphological change. Almost all of the thalli maintained at a constant extreme temperature of 29ºC died, but after being returned to optimum temperature conditions, the filamentous morphology began to develop from the surviving microscopic tissue. In contrast, thalli at a control temperature of 21ºC maintained the regular morphology throughout the experiment. When C. cylindracea develops this filamentous morphology, it may act as a cryptic invader because it is difficult to detect in the field. Furthermore, the filaments likely improve C. cylindracea´s invasive capabilities with regard to resistance, persistence and dispersion and may have an important role in the re-colonization process, after a population disappears following a period of stressful conditions. Possibly, C. cylindracea´s ability to respond plastically to stressful conditions might explain its remarkable success as an invasive species.